Study of biophysical mechanisms of aptamer-based biosensor for detection of Escherichia coli O157:H7 - Muhammad Fakhrullah Mohamad Azmi; Wan Mardhiyana Wan Ayub; Muhammad Fadzlisyam Redzuan; Irfan Danial Ismadi; Mohd Ifwat Mohd Ghazali; Muhamad Arif Mohamad Jamali; Liyana Azmi; Nur Zaireena Zainal; Nazefah Abdul Hamid; Shahino Mah Abdullah (Kolej PERMATA Insan, 2025)
International Conference And Innovation On Education, Science & Technology (ICIEST 2025) “Fostering Innovation And Creativity Through Education, Science & Technology” 21st June 2025 Editor : Hatika Kaco, Diani Mardiana Mat Zin, Fadzidah Mohd Idris, Siti Munirah Mohd Nurhidaya Mohamad Jan, Nor Atirah Izzah Zulkefli, Nadiah Suboh Organised by : Education & Advanced Sustainability (EdAS) unit, Kolej PERMATA Insan, Universiti Sains Islam Malaysia